JIT and supply chain management: an information processing perspective - Guilherme Guedes Xavier (Production)
Recently, as part of the restructuration of the global economy, new technologies and new consumer trends have led to changes in markets around the world. Based on this restructuration, some markets have faced extremely high degrees of competition, which led to the emergence of new concepts in the productive sector. One of the most important concepts was the spread of JIT systems outside Japan in the early 80s. Currently, another prominent concept, named supply-chain management is emerging In this paper, I take an information processing perspective to analyze both and conclude that, although complementary in dealing with uncertainties, both use different information processing strategies. Understanding the concepts and the relationship between them is important to their further development and diffusion among practioners and scholars' communities.